Unveiling the Connection Between Online Adaptive Learning and Learning Outcomes in Higher Education - Kurniawan, Citra; Dyah Utami, Deka; Susilaningsih, Susilaningsih; Mohd Nordin, Rumaizah; Surahman, Ence; Sumantri, Agus; Aniisah, Amiirah; Nur Hudha, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
Online learning is rapidly growing to meet diverse learning needs. However, the implementation of adaptive learning to better accommodate students' needs remains limited. This study aims to determine the direct relationship between the Frequency of Using Online Learning (FUOL) and the Duration of Using Online Learning (DUOL) on Learning Outcomes (LO), as well as the influence of Online Adaptive Learning (OAL) connectivity in the relationship between these two factors and Learning Outcomes (LO). The study found that FUOL does not have a direct effect on LO, and a similar result was observed for DUOL, which also does not directly affect LO. However, different results were found when adaptive learning strategies were applied to both FUOL and DUOL. The study found that OAL connectivity has an indirect effect on LO when combined with FUOL, while DUOL continues to show no significant effect. The implementation of Online Adaptive Learning is believed to impact student learning outcomes, although further research is needed to explore the role of internal factors such as motivation, self-efficacy, and student interest. These findings suggest that while online learning alone may not directly affect learning outcomes, the implementation of Online Adaptive Learning strategies can influence outcomes, particularly when linked to the frequency of online learning.